2016
DOI: 10.1039/c6ra19803a
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance of dye-sensitized solar cells based on modified kaolin/PVDF-HFP composite gel electrolytes

Abstract: The DSSCs based on modified kaolin/PVDF-HFP composite gel electrolyte have excellent efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…The result confirms the increased amorphisity in the irradiated polymer film. 31,32 This observation is in correlation with the XRD results.…”
Section: Resultssupporting
confidence: 87%
“…The result confirms the increased amorphisity in the irradiated polymer film. 31,32 This observation is in correlation with the XRD results.…”
Section: Resultssupporting
confidence: 87%
“…The peaks at 3448.64 and 1644.33 cm −1 (gray shadow marked) should be ascribed to OH stretching and bending vibrational absorption in the interlayer of KL. [ 38 ] With Zn embedded, the two peaks were significantly broadened along with increased intensity, suggesting that Zn 2+ may remain in the interlayer of kaolin with hydroxyl (Figure S8, Supporting Information). Compared with KL(Zn), the Mn‐embedded kaolin exhibited a similar but much smaller variation of those peaks, which confirmed that the Mn is only physically absorbed on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical functionalization decreases the NP aggregation, retaining a relatively large active surface area on the nanoparticles. This would, in turn, align the local density of to further accelerate the diffusion of the redox couple across the interconnected network structure of the GPEs [ 62 , 65 ]. Enhancement in kinetics of the dye regeneration by increasing the mobilization of the charge carriers added to the values of J SC , FF , and η .…”
Section: Resultsmentioning
confidence: 99%